Shrinkage considerations of morphometric measurements of little spiderhunter (Arachnothera Longirostra) - Nur Azlina, Ismail (Universiti Malaysia Sarawak, (UNIMAS), 2017)
This study focused on the little spiderhunter which is under Nectariniidae family. Frequently, morphometric study was conducted by using museum specimen. This study was designed to compare whether there are significant differences in percentage of observed shrinkages and percentage of randomized shrinkages in little spiderhunter. There were only two out of four of morphometric measurements (tarsus and total length) were randomized to 100, 1000, 10000 and 100000 by using randomization Exact Test. These two measurements have the highest values of discrimination when analyzed by using Discriminant Function Analysis (DFA). Both tarsus and total length showed significant differences between the observed percentages of shrinkages and randomized percentages. Little spiderhunter was found shrink about 2.72% for its tarsus and the percentages of randomized shrinkages were ranging from 0.37% to -0.02%. Then, the shrinkages of total length for little spiderhunters were 2.37% and ranging about 0.07% to -0.1% when they were randomized.